Competition for waterborne food resources among tropical shallow‐water sponges - Mark J. Butler; Steven E. McMurray; Joseph R. Pawlik (Ecology, 2025)
A recurrent theme in marine ecology is that the community dynamics of sessile, suspension‐feeding animals is primarily limited by the availability of space, but in some habitats, filtration by these organisms may locally deplete water column resources, setting the stage for exploitative competition for food. We examined filtration by sponge assemblages in the shallow waters (~2 m depth) of Florida Bay (Florida, USA), where water residence times are often high and filtration by dense communities of sponges was hypothesized to deplete the water column of food, primarily picoplankton and dissolved organic matter (DOM). We transplanted three sponge species into replicate locations that differed by an order of magnitude in natural sponge community biomass. Sponge transplants were clones, enabling us to control for sponge genotype effects across all sites. The growth of sponge clones was recorded seasonally for 18–30 months. Growth of transplants placed in areas devoid of sponges was 10 times greater than growth in areas with dense sponge communities and three times greater than growth in areas with average sponge biomass. Sponge mortality was similar regardless of background sponge density. Measurements of picoplankton, DOM, and PO 4 concentration confirmed an inverse relationship with sponge community biomass, whereas nitrogen concentrations in seawater were highest where sponge species replete with nitrogen‐fixing symbiotic microbial communities were most abundant. This is striking evidence that filtration of waterborne resources by sponges in shallow, coastal environments can deplete those resources sufficiently to cause exploitative competition that limits sponge growth.